FORMING STUDENTS' READINESS TO INTERCULTURAL COMMUNICATION IN TOURISM SPHERE: MAIN APPROACHES - Màiia Hàlytska; Nataliia Rekun (Borys Grinchenko Kyiv Metropolitan University, 2019)
The article analyzes the main approaches to forming students' readiness for intercultural communication in the tourism sphere, including: individual approach to students; problematic and creative nature of foreign language tasks; use of modern innovative learning technologies; dialogue of the learning process; modeling of professional communicative situations. The concept of «student's readiness for intercultural communication» is considered as an integrative professional characteristic of the individual, which determines the level of professionalism of the future specialist in his or her foreign language communicative competence and includes needs, motives, psychological qualities, subject and intellectual knowledge, skills and skills to perform professional tasks. It is concluded that foreign language is an important tool for intercultural communication and at the same time a special mechanism of effective cooperation, since it influences the process of formation of professional qualifications and competencies of future specialists in tourism industry, which ensures their competitiveness in the labor market and guarantees employment in the specialty.